ANALISIS MANAJEMEN EKSTRAKURIKULER FUTSAL DALAM MENINGKATKAN MINAT BAKAT SISWA MAN 1 TANJUNG JABUNG BARAT DENGAN MODEL CONTEXT, INPUT, PROCESS, PRODUCT (CIPP) - Nurkholis Ardinata; Wawan Junresti Daya; Anggrawan Janur Putra (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The purpose of this study was to determine the description of the management of futsal extracurricular activities at MAN 1 Tanjung Jabung Barat in improving students' interests and talents. This study uses the CIPP model with a qualitative approach method, where the researcher acts as the main instrument, namely a full observer and data collector. The sampling technique is Purposive Sampling, by collecting data from general informants, namely the Supervisor of futsal extracurricular activities, the Head of MAN 1 Tanjung Jabung Barat, and members of the futsal extracurricular activities of MAN 1 Tanjung Jabung Barat. The research subjects were interviewed and observed directly, because to match the data obtained through interviews with observations with triangulation techniques, so that the data collected reached the saturation level. The data results are arranged in the form of transcripts, then imported into Nvivo 12 software for further analysis. The data collected has been arranged based on the Context, Input, Process and Product (CIPP) components. The results of the study indicate that the management of futsal extracurricular activities at MAN 1 Tanjung Jabung Barat is positive in developing students' talents and interests, although not yet completely good and optimal. This study strengthens the CIPP model evaluation theory in the context of sports extracurricular management at the madrasah level. The four CIPP components (Context, Input, Process, Product) are interrelated in determining the success of the MAN 1 Tanjung Jabung Barat futsal extracurricular program.